The Influence of Learning Motivation, Learning Style, and Learning Environment on Learning Outcomes of Class V Students - Dimas (Program Studi Manajemen Pendidikan, 2024)
This research aims to analyze the influence of learning motivation, learning style, and learning environment on social studies learning outcomes for class V students. The type of research used in this research is quantitative research (Ex Post Facto). The subjects used in this research were class V students with a total of 83 class V students in Gugus I Panakkukang District, Makassar City. The instruments used in this research are instruments, namely tests, questionnaires, tests and documentation. The data analysis techniques used were descriptive tests and inferential tests (normality, linearity, multicollinearity, path analysis, simple and multiple regression). Based on data analysis using SPSS 25, the normality test using Kolmogorov-Smirnov is sig > 0.05, while the multiple regression test obtained shows a significance value of 0.000. 0.000 < 0.05 then